CATASTROPHIC EXPLOSIVE VOLCANIC ERUPTIONS IN KAMCHATKA AND THE KURILE ISLANDS IN LATE PLEISTOCENE-EARLY HOLOCENE TIME - Melekestsev I.V.; Braytseva O.A.; Sulerzhitskiy L.D. (My University, 1988)
Geologic, geomorphic and tephrochronologic data and the results of C14 dating indicate that in Kamchatka and the Kurile Islands in the last 40,000 to 45,000 years there were at least 50 very powerful explosive eruptions from 32 to 35 volcanic centers, and that each of them deposited 5 to 150 km3 of pyroclastic material on the surface. During those eruptions, pyroclastic flows formed pumice, tuff and ignimbrite sheets and spread as far as 50 to 60 km away from the volcanic centers across an area on n·102 to n·103 km2, while tephra thicker than 1 cm fell onto an area of n·104 to n·106 km2 not only on the land, but also in the sea as far as 500 to 1000 km from the coast. Such eruptions can be classified as catastrophic on the basis of their parameters. The eruptions studied were clearly confined to two paroxysms of explosive volcanism, late Pleistocene and early Holocene. The more powerful and longer paroxysm occurred from 45,00 to 25,000 B.P., and the younger and shorter one between 9500 and 7000 B.P.
Keywords: Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Голоцен